Pengaruh Pendidikan, Literasi Keuangan dan Gaya Hidup terhadap Pengelolaan Finansial pada Mahasiswa Akuntansi Universitas 17 Agustus 1945 Surabaya - Diah Indri Anggriyanti; Hwihanus Hwihanus (Jurnal Riset Akuntansi, 2024)
Effective financial management is an important part of life, especially for students who are heading towards financial independence. This study aims to provide an analysis of the influence of educational factors, financial literacy and lifestyle on the financial management of accounting students at the University of 17 August 1945 Surabaya. In this data analysis is carried out by observing the answers to the questionnaires that have been filled out and interviewing a number of students from the accounting study program. Using qualitative methods can gain a comprehensive understanding of how these factors interact and shape students' financial management practices. The results show that accounting education provides a strong theoretical foundation, based on the inclusion of certain research findings, but is not always directly proportional to the daily practice of financial management. Low levels of financial literacy are often a major obstacle, especially when it comes to long-term financial planning. Consumptive lifestyles are also an important factor in students' financial decisions. In addition, the study also found that social factors such as family and peer influence also affect students' financial behavior as well. This research provides a better understanding of the causes that influence college students' financial management. The results of this study can serve as a foundation for developing more relevant and effective financial education programs and provide recommendations for accounting students to better manage their finances. Researchers also hope to contribute to the development of student financial management literature, especially accounting students. The results of this study can also provide references for educational institutions, universities, and other financial institutions to design programs to improve student financial literacy.